Workplace Bullying and its Impact on Employees’ Morale - Humza, Namra (Archives of Business Research, 2023)
The problem of workplace bullying is one of the most important issues facing society and companies in particular. Many scholars have identified the problem as abuse, fear, harassment, and persecution. Bullies may also be co-workers, clients, customers, suppliers, bosses, and supervisors. Workplace bullying may be seen as a certain, somewhat frequent, unfavourable dynamic that occurs over time in companies. Bullying at work has been linked to various workplace-related problems, including poor health outcomes, decreased job satisfaction, organizational commitment, and increased intention to quit. Bullying is a serious workplace issue that harms both the environment and the workers. This research synthesizes the literature on workplace bullying and how it affects employee morale, productivity, and satisfaction in light of these negative effects of bullying at work.